Empirical performance-comparison of E2E dual-stack IP protocol method over wired and wi-fi broadband access / Wan Mohd Nazmin Wan Mahmud - Wan Mahmud, Wan Mohd Nazmin (2016)
Due to the depletion of the current IPv4 address pool of Internet addresses and the desire to provide additional functionality and enhancement, an upgrade of the original version of the Internet Protocol (IP), called IPv6, has been standardized. This new version, called IP version 6 (IPv6), resolves unanticipated IPv4 design issues and takes the Internet into the 21st Century. IPv6 performance is still uncertain of several ISPs for the adoption IPv6 in their networks while maintaining the existing IPv4 addresses. Thus, it is very essential to evaluate the performance of E2E IPv6 network. This paper present the empirical performance of IPv6 over wired and Wi-Fi broadband access in comparison with IPv4. Real network environment used to provide a comparative performance of a comprehensive dual-stack IP method in one of the major fixed broadband provider in Malaysia. The real E2E Dual-Stack IP of a Client Server test-bed for instance as an actual baseline from an end-user perspective for future research and guidelines for Dual-Stack implementation. Performance evaluation and comparison is based on RTT, FTP, IPerf performance test tool and High-throughput TCP test by using Ixia IxChariot test gear. Generally, performance comparison results affirm that Dual-Stack IP method as a more reliable protocol to opt in a real network environment. In addition, IPv6 represent throughput higher than IPv4 and more robust in transaction rate based on RTT, FTP, IPerf and Ixia IxChariot measurement results.